PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN MENULIS POSTER - Qomsiatun Qomsiatun; Herman Budiyono; Eddy Pahar Harahap (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the application of a project-based learning model to improve the process skills and learning outcomes of class VIII students at Al Falah Islamic Junior High School, Jambi City. The researcher used a research method in the form of classroom action research (PTK), data collection techniques using observation instruments, interviews, documentation, and poster writing assignments. The research subjects were students of class VIIIl 1 SMPl Islam All Falah Kotal Jambi, with a total of 28 students. The variables in the study were the learning process and the results of writing posters using a project-based learning model. The results of this research showed that the pre-action average was less than the minimum completeness criteria (KKMl) set, which is 75. The pre-action average was 72.1, and cycle I reached 77.5. In cycle II, it increased to 80.9 and reached the predetermined limit of completeness. It was concluded that the application of the project-based learning model with observation of the process and product results of learning to write posters showed a significant improvement.